ENHANCING STUDENTS' CRITICAL THINKING THROUGH NASA SCIENCE AS INTERACTIVE MULTIMEDIA IN LEARNING SOLAR SYSTEM - Nurul Azizah Al Mar' Ati, - (2020)
Science and technology advancement in the 21st Century requires several life skills that everyone must learn, one of which is Critical Thinking. Critical thinking skill is often defined as a process of metacognitive which consists of several sub-skills (e.g., analysis, inference, and evaluation) that increase the chances of solving a problem or producing a logical conclusion to an argument. This research attempted to implement NASA Science as Interactive Multimedia to enhance students' critical thinking in learning Solar System. Interactive Multimedia is student-centered, allowing students to play an active role in deciding how to learn to promote the critical thinking skills of students. This study used a pre-experimental method with one group pretest-posttest design. The sampling used was convenience sampling, which participated in 42 7th grade students of a private school in Bandung. The Objective Test was used as a research instrument for both pretest and posttest. These test items were designed according to Facione's indicators of Critical Thinking Skills. Based on the analysis result, the value of n-gain is 0.48. According to the Wilcoxon Signed Rank Test, the hypothesis in this research was accepted. The value of Asymp. sig. (2-tailed) is 0.00, with a sig. α = 0.05. Thus, the result of this research shows that: There is an enhancement of students' critical thinking after using NASA Science in learning Solar System.